SISTEM INFORMASI PENGOLAHAN DATA TINDAK KRIMINALITAS PADA POLRESTA JAMBI: Application, Criminal, Data Processing, Data, Website - Nurjani, Yeni; Heranda, Dufan (FORTECH (Journal of Information Technology), 2025)
The use of information technology in the National Police, such as the Criminal Investigation Information System application at the Jambi City Police, helps in processing police report data and handling criminal cases. However, challenges still exist because data processing is still manual, creating delays in reporting and investigating cases. Therefore, an application was created, "Criminal Data Processing Information System at the Jambi City Police based on Android," to speed up the process and make it easier for the public to report criminal cases. The objectives of this study are to help the process of serving criminal reports from manual to digital, processing data into information that can be useful for related parties, and making the process of making criminal reports more dynamic so that it becomes more effective and efficient. The study uses the waterfall method for systematic software development, starting from needs analysis to maintenance, with sequential stages: requirements, system design, coding & testing, program implementation, and maintenance. The overall conclusion of the Android-based Crime Information System Design application is that it helps crime victims, law enforcement in data management, and provides information on crime-prone areas.